Breast cancer screening in germline mutation carriers. A literature review - A. V. Sultanbaev; A. F. Nasretdinov; M. G. Galeev; K. V. Menshikov; Sh. I. Musin; N. I. Sultanbaeva; R. T. Ayupov; R. R. Rakhimov; O. N. Lipatov; A. A. Izmaylov; I. A. Menshikova; G. A. Serebrennikov; et al. (Опухоли женской репродуктивной системы)
Carriers of germline mutations have an increased risk of developing malignant neoplasms. Mutations in the BRCA1/2 gene are the most studied, leading to an increased risk of breast cancer, characterized by early manifestation and aggressive course. The development of screening measures aimed at identifying tumors characteristic of certain mutations will increase the patient’s chances for radical treatment, and therefore lower costs for the treatment of advanced forms of malignant neoplasms. It is important to know the correlation of mutations with the characteristics of their clinical manifestation, the study of this issue will lead to the formation of a medical and economic justification for additional diagnostic procedures.